2006
DOI: 10.3748/wjg.v12.i5.776
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β gene polymorphism associated with hepatocellular carcinoma in hepatitis B virus infection

Abstract: IL-1B-511C allele, which may be associated with high IL-1B production in the liver, is a genetic marker for the development of HCC in chronic hepatitis B patients in Thai population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 36 publications
4
43
3
Order By: Relevance
“…Some studies showed that IL-1b À511 C haplotype is associated with advanced liver disease. 14,34 In the present study, genotype CC was found to be higher in asymptomatic cases, no significant difference in the proportions of CT or TT genotypes in other clinical categories was observed. Interestingly, it was observed that genotype CC category was associated with significantly lower HBV titer ( Figure 1) as well as with relatively low ALT.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Some studies showed that IL-1b À511 C haplotype is associated with advanced liver disease. 14,34 In the present study, genotype CC was found to be higher in asymptomatic cases, no significant difference in the proportions of CT or TT genotypes in other clinical categories was observed. Interestingly, it was observed that genotype CC category was associated with significantly lower HBV titer ( Figure 1) as well as with relatively low ALT.…”
Section: Discussioncontrasting
confidence: 67%
“…Polymorphism in the IL-1b À511 promoter region and IL-1RN gene VNTR are reported to be associated with varying degree of HBV associated clinical prognosis. 11,14 Another study from Iran found no association of IL-1RN gene polymorphism with the development of chronic HBV infection. 15 Hence the association of the above mentioned polymorphic genetic factors with HBV associated clinical outcome seems to vary from one population to another.…”
Section: W Orldwide Hepatitis B Virus (Hbv) Associatedmentioning
confidence: 99%
“…Numerous studies have investigated the relations between cytokine polymorphisms and HCC risk; however, their results are controversial (Shin et al, 2003;Hirankarn et al, 2006;Slattery et al, 2007). Two studies have consistently noted that IL-1β-511 polymorphisms are significant risk factors for HCC progression in the Thai population and in Japanese patients (Tanaka et al, 2003;Hirankarn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Two potentially functional SNPs (-511T/C and -1464C/G) in the promoter region of IL-1β can increase IL-1β production (Zeng et al, 2003). The promoter region of IL-1β is reportedly associated with the risk of developing cancers of the lung (Zienolddiny et al, 2004), breast (Liu et al, 2006), liver (Hirankarn et al, 2006), and stomach (El-Omar et al, 2000). IL-2 exerts pleiotropic effects on the immune system by acting as a pro-and anti-inflammatory regulator.…”
Section: Introductionmentioning
confidence: 99%
“…2. High IL-6 levels are associated with a reduction in HBV replication and IL-1 is important in many inflammatory processes associated with HBV infection, including HCC (Hirankarn et al 2006, Kuo et al 2009). However, IL-1 and IL-6 levels were undetectable in the study groups.…”
Section: Analysis Of Pro-inflammatory Cytokines In Ohb-mentioning
confidence: 99%